Estimating the elasticity of intertemporal substitution using dividend tax news shocks - Martin Blomhoff Holm; Rustam Jamilov; Marek Jasinski; Plamen T. Nenov (Norges Bank, 2024)
This paper studies the spending response to news about a dividend tax reform to estimate the elasticity of intertemporal substitution (EIS). The Norwegian dividend tax reform was proposed in 2003, announced in 2004, and implemented in 2006, raising the dividend tax rate by 28 percentage points. We compare the spending responses of exposed households to a control group with no dividend income. Exposed households increased spending after the news and reduced spending after implementation. We show that this behavior is only consistent with an EIS above one. Using a capitalistworker framework, we estimate the EIS to be around 1.6.
hdl:11250/3177100
Keywords: D15; E21; H25; 330; Anticipatory dis-saving; capital income taxation; capitalist-worker model; impulse response matching